Design and Synthesis of Some Nitrate Derivatives of Mefenamic Acid with Expected Nitric Oxide Release - A. Sadon, Ahmed; J. Qasir, Ahlam (Iraqi Journal of Pharmaceutical Sciences, 2017)
This study include design and synthesis of 2 derivatives of compounds consisting of mefenamic acid, glycine and organic nitrates (2-nitrooxy ethanol or 1,3-dinitrooxy-2-propanol). Nitric oxide NO has been reported to support many of the same mucosal protection mechanisms as prostaglandins and is sufficient for acute gastroprotection and ulcer healing. So we suppose these 2 compounds would reduce non-steroidal anti-inflammatory drugs NSAIDs gastrointestinal side effect.Key words: Non-Steroidal anti-inflammatory drugs (NSAIDs), Glycine, Mefenamic acid, Organic nitrates, Nitric oxide (NO).